Moedas locais: uma investigação exploratória sobre seus potenciais como alternativa à exclusão financeira a partir do caso do Banco Bem em Vitória/ES - Melissa Silva Menezes (2007)
The aim of this paper is to investigate towards a relatively unexplored area: the Local Money Systems (LMS), that are, in short, an agreement amongst the population of a community to use a mean of payment which is valid only in that particular space where they live. These experiences are widely relevant, as well as the variety of the objectives that lead to the creation of the referred currency. Thus, the attempt here is to point out for the existence of this phenomenon worldwide, setting up the basis for the development of further academic research in this respect. Moreover, we tried to associate, in theory and practice, the occurrence of the local money with the exclusion of its users from the conventional financial system.To achieve such objectives, it was made a survey of the existent national and international bibliography on this topic, an exercise of theorization based on the post-keynesian theory and an exploratory study of a brazilian case, the Banco Bem located in the city of Vitoria/ES. The goal was not to infer concluding results - which would be precipitate because of its early character - but to expand its understanding and to indicate its potentialities and limits.The outcome suggests that the local currencies are perceived as a manner to confront not only the financial exclusion but also the economic and social exclusion. Far from being the solution for the problems caused by the capitalist concentration, the LMS must be seen as an attempt to soften the precarious situation of those that are excluded.